Publicly funded Steiner education in England–Beautiful anomaly? Missed opportunity? Or both? - Mepham, Trevor Michael (Frontiers in Education, 2024)
This paper reflects on an educational policy initiative taken by the New Labour Government in England in the 1990s–2000s to extend parental choice in publicly funded school education, and to widen social access to different educational approaches. As such, the policy which led to the opening of a Steiner Academy School in Herefordshire contained elements of educational diversity and inclusion, a degree of parental choice that had not been considered previously, and an extending of social access to different and distinctive educational approaches. For example, in the case of the Steiner Academy Hereford, the National Curriculum for schools in England was set aside in favour of the Steiner Waldorf curriculum framework. The paper seeks to set out the main features of the negotiation that led up to the state funding of Steiner education in England, along with an exploration of the processes, compromises, achievements and setbacks that were encountered along the way.